Eyetracker analysis of fixation points using an IR HUD in an automobile. (29th October 2004) - Meitzler, Thomas; Lane, Kimberly; Bryk, Darryl; Sohn, E.J.; Jusela, Daniel; Ebenstein, Samuel; Smith, Greg; Rodin, Yelena
This paper describes the experimental apparatus and analysis techniques now in place at the US Army Tank-automotive and Armaments COMmand Visual Perception Lab in Warren, Michigan, and the results of some preliminary trials using these methods. The tools will be used to develop and analyse experiments to better understand how drivers use various displays and viewing systems intended to aid drivers in poor visibility conditions, particularly at night. Visible and infrared road scene imagery obtained from the field were displayed simultaneously and subject eye fixation and point of gaze measured using a magnetic head tracker and near infrared eyetracker. Results were analysed to determine if personal differences between the various subjects caused them to prefer one display to another. The goal was to see if people prefer to use the heads up display or the direct view for driving at night.